New, precarious adulthood: kidults in the ‘crowded nest’ - Bieńko, Mariola (Studia Demograficzne, 2020)
In the period of young adulthood, i.e., between ages 18–20 and 30–35, the coupling of the duties, goals, and ambitions connected with various life activities takes place, these being in education, participation in the labour market, self-supporting a household, starting a family, becoming a parent, and active participation in the social life. The social and cultural as well as economic changes that are occurring nowadays affect the course of family life as well as the stages of individual development. One of these stages refers to a young adult leaving the family home. However, it is more and more often the case that this moment gets deferred. Research conducted by sociologists and demographers in the recent years shows that the growing share of young people in industrialised countries choose to live with their parents in spite of their adult age. The increase in young adults staying in the family home in the recent years has led to the term ‘nesters’ being coined for them, while the effect of their bond with their guardians being stretched in time is now referred to as the ‘crowded nest’ or ‘cluttered nest’. This article offers an insight into one of the components of the process of reaching adulthood, namely leaving parental home. The qualitative study (carried out in 2012 and 2013) combines statistical analyses and personal interviews; its results are based on 42 interviews with women and men aged between 27 and 38 who live with their parents in Warsaw, Poland. This interview-based analysis focuses on demonstrating the process of nesting of young adults and the interviewed persons’ perception of this behaviour.